2020
DOI: 10.7717/peerj.10204
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of diploid and triploid Populus tomentosa

Abstract: Triploid Chinese white poplar (Populus tomentosa Carr., Salicaceae) has stronger advantages in growth and better stress resistance and wood quality than diploid P. tomentosa. Using transcriptome sequencing technology to identify candidate transcriptome-based markers for growth vigor in young tree tissue is of great significance for the breeding of P. tomentosa varieties in the future. In this study, the cuttings of diploid and triploid P. tomentosa were used as plant materials, transcriptome sequencing was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…At the same leaf position, genes related to photosynthesis-and chlorophyll-related processes were upregulated in triploid populus. Similarly, genes related to the synthesis and transduction of hormones, such as auxin, mitogen, and brassinolide, were also upregulated, which led to speculation that the molecular mechanism that enhances photosynthesis and possible synthesis and transduction of plant hormones was the reason for its fast growth [16][17][18]. Liao et al [19] also found that after chromosome doubling, hormones such as auxin, CK, and GA increased in populus.…”
Section: Introductionmentioning
confidence: 99%
“…At the same leaf position, genes related to photosynthesis-and chlorophyll-related processes were upregulated in triploid populus. Similarly, genes related to the synthesis and transduction of hormones, such as auxin, mitogen, and brassinolide, were also upregulated, which led to speculation that the molecular mechanism that enhances photosynthesis and possible synthesis and transduction of plant hormones was the reason for its fast growth [16][17][18]. Liao et al [19] also found that after chromosome doubling, hormones such as auxin, CK, and GA increased in populus.…”
Section: Introductionmentioning
confidence: 99%
“…Triploid Chinese white poplar ( P. tomentosa Carr., Salicaceae ) has stronger advantages in growth and better stress resistance and wood quality than diploid P. tomentosa . The expression levels of CYCD3 in triploid P. tomentosa are higher than those in diploid P. tomentosa 61 . Transgenic PtoCYCD3;3 makes poplar leaves large and curled, increases plant height and stem diameter 12 .…”
Section: Discussionmentioning
confidence: 77%
“…PRJNA786265). Transcriptome assembly, sequence alignment, gene orthology determination, and gene set enrichment analysis were performed according to the method described by Bian [ 21 ]. Differential gene expression heat maps were plotted using Log2 (Fragments Per Kilobase of Exon Model per Million Mapped Fragments (FPKM) + 1) values with the R 3.0.2 software.…”
Section: Methodsmentioning
confidence: 99%